(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Studying the effect of clothing on thermoregulatory responses of human body is highly complex because clothing, resp. a clothing system, as a heat exchange layer between the body and the environments must ensure a balance between heat production and heat dissipation within different environments and during various activities. The problem becomes more complex in the case of protective clothing, which requires liquid penetration resistance or impermeability of the material, restricting thus the dry heat flux by conduction, convection, and radiation, as convection and conduction transfer of heat caused by sweat evaporation and condensation. This paper deals with the study of the impact of clothing as baseline clothing, made from different functional materials, on thermoregulatory responses of human body in the limited heat and moisture transfer context. The results of the investigation show that the effect of baseline clothing, as an interface layer, worn under impermeable protective clothing, on thermoregulatory responses of human body, is limited during wearing in a hot environment.